Enhancing Writing Skills Through Chat GPT: A Literature Review - Susanti, Arik; Azizan, Ahamad Tarmizi (Proceeding of International Joint Conference on UNESA, 2025)
This investigation investigates the utilization of Chat GPT as an instrument for improving the writing abilities of EFL (English as a Foreign Language) students in Indonesia. The paper explores the potential of Chat GPT, an AI-based technology, to enhance students' descriptive text writing skills by incorporating it into classroom instruction through a literature review. The paper investigated the obstacles encountered by Indonesian learners, including obstacles in the use of appropriate tenses, punctuation, and the expression of ideas. The research underscores that conventional teaching methods frequently fail to captivate students; conversely, Chat GPT provides learners with immediate feedback, alleviates anxiety, and fosters creativity. Chat GPT cultivates a more interactive and engaging learning environment by assisting students in ideation, outlining, and enhancing their grammar and vocabulary. The results emphasize the beneficial effects of Chat GPT on writing motivation and creativity, indicating its potential as a valuable tool for teaching writing skills. The study concludes by suggesting that additional empirical research be conducted to investigate the more extensive implementation of Chat GPT in educational environments.